ANALISIS EFEKTIVITAS PROGRAM PENGOLAHAN WIRAUSAHA PESANTREN AL FATH KENDARI DALAM MENINGKATKAN KETERAMPILAN DAN JIWA WIRAUSAHA SANTRI - Wahidin, La Ode; Husriadi, Muh.; Hasan, Hasni; Aswin, Muhammad (Jurnal Valuasi: Jurnal Ilmiah Ilmu Manajemen dan Kewirausahaan, 2025)
Al Fath Kendari Islamic Boarding School has an entrepreneurial processing program that aims to improve the skills and entrepreneurial spirit of students. This study aims to analyze the effectiveness of the program in achieving its goals. The research method used is qualitative with a descriptive approach. Data was collected through interviews, observations, and documentation. Interviews were conducted with related parties, such as Islamic boarding school caregivers, entrepreneurial program administrators, and students participating in the program. Observations were carried out at the location of entrepreneurial programs and student entrepreneurial activities. The documentation collected is in the form of entrepreneurial program materials, program activity reports, and student entrepreneurial products. The results of the study show that the entrepreneurial processing program of the Al Fath Kendari Islamic Boarding School is quite effective in improving the skills and entrepreneurial spirit of students. This is evidenced by the increase in knowledge, attitudes, and skills of students in entrepreneurship. Students' knowledge about entrepreneurship has increased significantly after participating in the program. Students become more aware of the concept of entrepreneurship, types of businesses, and strategies for starting and running a business. The attitude of students towards entrepreneurship has also undergone positive changes. Students become braver to take risks, creative in looking for business opportunities, and never give up in facing challenges. The skills of students in entrepreneurship have also improved. Students are able to make business plans, conduct market analysis, and manage their business finances. The entrepreneurial processing program of the Al Fath Kendari Islamic Boarding School is quite effective in improving the skills and entrepreneurial spirit of students. This program can be a model for other Islamic boarding schools in developing entrepreneurial programs for students